The short chain fatty acid receptor GPR43 regulates inflammatory signals in adipose tissue M2-type macrophages - Nakajima, Akira (PLoS One, 2017)
The regulation of inflammatory responses within adipose tissue by various types of immune cells is closely related to tissue homeostasis and progression of metabolic disorders such as obesity and type 2 diabetes. G-protein-coupled receptor 43 (GPR43), which is activated by short-chain fatty acids (SCFAs), is known to be most abundantly expressed in white adipose tissue and to modulate metabolic processes. Although GPR43 is also expressed in a wide variety of immune cells, whether and how GPR43 in adipose tissue immune cells regulates the inflammatory responses and metabolic homeostasis remains unknown. In this study, we investigated the role of GPR43 in adipose tissue macrophages by using Gpr43-deficient mice and transgenic mice with adipose-tissue-specific overexpression of GPR43. We found that GPR43 activation by SCFA resulted in induction of the pro-inflammatory cytokine tumor necrosis factor-α (TNF-α) in anti-inflammatory M2-type macrophages within adipose tissue. By contrast, this effect was not noted in inflammatory M1-type macrophages, suggesting that GPR43 plays distinct functions depending on macrophage types. Local TNF-α signaling derived from steady-state adipose tissue is associated with proper tissue remodeling as well as suppression of fat accumulation. Thus, GPR43-involving mechanism that we have identified supports maintenance of adipose tissue homeostasis and increase in metabolic activity. This newly identified facet of GPR43 in macrophages may have clinical implications for immune-metabolism related episodes.